Bre index for the Hong Kong residential property market - Hui, Eddie Chi Man; Wong, Joe Tak Yun (International Journal of Strategic Property Management, 2010)
This paper examines housing price trends and prediction, of homeowners and potential home buyers, and establishes an independent index (the BRE Index) based on longitudinal telephone surveys collected. The Index, first of this kind in Hong Kong, measures price expectations and benchmarks the level of housing actors’ confidence in the residential market. This is the first paper delivered as part of a government‐funded research project. It synthesizes the key findings of the first survey mounted from 17th to 20th December, 2003. The results show that confidence among housing actors has begun to grow since the property crash in late 1997 with the “overall” BRE Index standing at 564 (0–1000 range). In general, homeowners, people with higher educational level and higher income are optimistic about the market outlook. Residential property prices are expected to rise marginally in the short term. Statistically, there is no significant difference in housing price expectations between homeowners and non‐owners. In their minds, economic condition is the most important factor affecting housing decisions. Apparently, the rising trends in the immediate past have been used to form expectations. The strength of the association between actual capital gains and forecast capital gains is moderately strong, and there appears co‐movement between them. This leads us to believe that hope‐led expectations increase the likelihood of sustaining price increases. The current market is largely driven by expectations. If households formed their expectations in a similar manner in other periods, there would be similar “positive hit” results, which might render the Index more powerful.First Published Online: 18 Oct 2010